2015
DOI: 10.1016/j.rmed.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1 and progression of percent emphysema: The MESA Lung Study

Abstract: Endothelial intercellular adhesion molecule (ICAM) 1 binds neutrophils and facilitates their transmigration into the lung; E-selectin facilitates leukocyte rolling. As neutrophils contribute to tissue destruction in emphysema and chronic obstructive pulmonary disease, we hypothesized that soluble ICAM-1 (sICAM-1) and E-selectin (sE-selectin) would be associated with longitudinal progression of emphysema and lung function decline. The Multi-Ethnic Study of Atherosclerosis (MESA) enrolled participants 45-84 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…MAC-1 binds to intracellular adhesion molecule-1 (ICAM-1) on the surface of endothelial cells. Serum levels of ICAM-1 are inversely related to lung function and are also associated with increased percentages of emphysema on CT scan suggesting that this mechanism may be clinically relevant [18, 19]. Blocking the action of ICAM-1 in rodent models has also reduced pulmonary inflammation further supporting the possibility that the increase in ICAM-1 might be related to the increase in inflammation seen in COPD [20].…”
Section: Introductionmentioning
confidence: 99%
“…MAC-1 binds to intracellular adhesion molecule-1 (ICAM-1) on the surface of endothelial cells. Serum levels of ICAM-1 are inversely related to lung function and are also associated with increased percentages of emphysema on CT scan suggesting that this mechanism may be clinically relevant [18, 19]. Blocking the action of ICAM-1 in rodent models has also reduced pulmonary inflammation further supporting the possibility that the increase in ICAM-1 might be related to the increase in inflammation seen in COPD [20].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of sICAM-1 were associated with accelerated progression of emphysema in MESA, indicating that neutrophil recruitment to the lung, mediated by ICAM-1, may play a role in the progression of subclinical emphysema[12]. Similarly, higher levels of P-selectin were associated with peripheral arterial disease, suggesting that leukocytes recruitment to sites of vascular injury, mediated by P-selectin, may contribute to progression of peripheral arterial disease.…”
Section: Biomarker Domains Measured In Mesamentioning
confidence: 99%
“…To provide context, other assessments of emphysema progression in non-HIV cohorts which have used a quantitative rather than qualitative approach through lung densitometry measurements have found that lower BMI[28], current smoking status[29], and female sex[29] are associated with more rapid emphysema progression. Circulating biomarkers such as soluble intercellular adhesion molecule (ICAM-1)[30], surfactant protein D[29] and soluble receptor for advanced glycation end product (sRAGE)[29] have also been shown to be higher in more rapid emphysema progressors.…”
Section: Discussionmentioning
confidence: 99%